If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 3 = x Combine like terms: -3 + 3 = 0 0 = x Solving 0 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 0 + -1x = x + -1x Remove the zero: -1x = x + -1x Combine like terms: x + -1x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 14x-6=8x-18 | | 10+3x=35-2x | | 2a-1=4+a | | 6x-5+5x=120 | | 2x+10=22-x | | 5p+4q=40 | | 8-3p+5p=1-p | | 5+6x=17-6x | | 9c(2)-18c+8=0 | | 8t-1=23-4t | | 9+2x= | | 7x-2=5x+1 | | 5x-4=3x+26 | | 15-5x=3-2x | | 3x+1/2=11 | | 5x-7+x+5+2x-1=180 | | 5x-6=10x-36 | | 4m-7=3m | | 5(x-2)+2x=9x-2(3x-5) | | 11y+16-9y-9+2y=47 | | 2x-12=6x-12 | | 128+8=42+28 | | 11+6x=2x-5 | | 6x+11=8x-9 | | 8p+5q=10 | | -57-2X=8X+22 | | 5-3x=5x-19 | | 2+7=11 | | 17-x=6x-11 | | 2a^2+12a=-24 | | -57-2X=5X+16 | | 10-2x=13-5x |